Profiling the technical tactical components of performance in professional soccer. - Joseph Benjamin Taylor (2006)
Soccer has received considerable interest within the existing notational analysis literature with particular focus upon the technical and tactical components of performance. Much of this research has however been limited by conceptual and methodological issues such as the failure to adopt rigorous performance profiling techniques and the use of inadequate data analysis procedures. The purpose of this thesis therefore was to profile the technical and tactical components of soccer performance via a case study of a professional British team using robust methodologies and advanced statistical techniques. All data were collected from match recordings provided by the participating soccer club using the computerised Noldus Observer Video Pro 4.1 behavioural measurement package (Noldus Information Technology, 2002). In Study 1 and Study 2 respectively, technical and tactical measures of 'on-the-ball' performance were developed and validated by professional soccer coaches and experienced notational analysts. The technical aspect of performance was subsequently assessed by constructing behavioural and outcome profiles corresponding to behaviour incidence and success rates. Tactical performance was investigated via the development of spatial profiles relating to the occurrence of the technical behaviours across the pitch surface. Collectively, the findings highlight the need to examine soccer performance at the team, playing position and individual player level to account for the inter- and intra-positional technical and tactical differences within the sport. Based upon the profiles produced within Study 1 and Study 2, Study 3 utilised advanced statistical modelling procedures to examine the potential influence of a number of situation variables upon the technical and tactical components of soccer performance. Log-linear and logit modelling revealed significant main effects and interactions of match location, opposition quality and match status upon behaviour incidence (technical), behaviour occurrence across the soccer pitch surface (tactical) and to lesser extent behaviour outcomes (technical). These findings suggest that potential 'confounding' variables need to be considered when making evaluations and predictions associated with the technical and tactical elements of soccer performance. Overall, the findings of this thesis have facilitated a greater understanding of the profiling of the technical and tactical components of soccer performance through using rigorous methodologies and advanced statistical procedures. Practical implications for soccer coaches and notational analysts are discussed in relation to the scouting of opposition teams and players, and evaluation and prediction of performance. Future soccer-based notational analysis research should consider profiling the technical and tactical components of 'off-the-ball' behaviours and examine the influence of additional 'confounding variables' upon performance.